2011
DOI: 10.1021/jm101642g
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interactions of Fluorinated Nucleotide Derivatives Targeting Orotidine 5′-Monophosphate Decarboxylase

Abstract: Fluorinated nucleosides and nucleotides are of considerable interest to medicinal chemists due to their antiviral, anticancer, and other biological activities. However, their direct interactions at target binding sites are not well understood. A new class of 2′-deoxy-2′-fluoro-C6-substituted uridine and UMP derivatives were synthesized and evaluated as inhibitors of orotidine-5′-monophosphate decarboxylase (ODCase). These compounds were synthesized from the key intermediate, fully-protected 2′-deoxy-2′-fluorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Subsequent hydrolysis reaction and fluorination with DAST reagent gave rise to the compound 3 in 64% overall yield. The deprotection of 2′-deoxy-2′-fluoro-3′,5′-di- O -tetrahydropyranyl-β- l -uridine could be realized by treatment with either p -TsOH in MeOH at room temperature for 3 h or with Amberlite (H + ) in aqueous methanol overnight . However, we found that the first method generated traces of p -toluenesulfonic acid that might catalyze detritylation reaction and reduce the yield of the target compound.…”
mentioning
confidence: 99%
“…Subsequent hydrolysis reaction and fluorination with DAST reagent gave rise to the compound 3 in 64% overall yield. The deprotection of 2′-deoxy-2′-fluoro-3′,5′-di- O -tetrahydropyranyl-β- l -uridine could be realized by treatment with either p -TsOH in MeOH at room temperature for 3 h or with Amberlite (H + ) in aqueous methanol overnight . However, we found that the first method generated traces of p -toluenesulfonic acid that might catalyze detritylation reaction and reduce the yield of the target compound.…”
mentioning
confidence: 99%
“…This huge difference indicates that the side chain of Lys-72 interferes with UMP binding and thereby significantly weakens the affinity between WTODCase and its product, consequently supporting product release. However, when lysine is replaced by alanine in the K72A mutant, the binding strength of UMP is second only to that of 6-hydroxy-UMP, the best ODCase inhibitor known (9,20,(31)(32)(33)(34)(35)(36). This adds strong product inhibition to loss of transition state stabilization as explanations for the high reduction in catalytic potency of the K72A mutant enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Because de novo synthesis of pyrimidine nucleotides is upregulated during abnormal cell growth or during the replication of cells, when the demand for pyrimidine nucleotides is high, the ODCase can be considered as one of the potential anticancer targets. 7 In fact, in the last decades a significant interest has been given to ODCase as a drug target for a number of modified nucleos(t)ide analogues, in particular C6-substituted UMP derivatives also in the antiviral and antimalarial arena. [7][8][9][10] This is due to a pivotal role that ODCase plays in the de novo synthesis of pyrimidine nucleotides such as uridine-5'-O-monophosphate (UMP, 2) from orotidine-5'-O-monophosphate (OMP, 1, Figure 1) via decarboxylation 6a and its extraordinary reaction rate enhancement (over 17 orders of magnitude) in comparison with spontaneous uncatalyzed decarboxylation of OMP observed in water at neutral pH and ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…7 In fact, in the last decades a significant interest has been given to ODCase as a drug target for a number of modified nucleos(t)ide analogues, in particular C6-substituted UMP derivatives also in the antiviral and antimalarial arena. [7][8][9][10] This is due to a pivotal role that ODCase plays in the de novo synthesis of pyrimidine nucleotides such as uridine-5'-O-monophosphate (UMP, 2) from orotidine-5'-O-monophosphate (OMP, 1, Figure 1) via decarboxylation 6a and its extraordinary reaction rate enhancement (over 17 orders of magnitude) in comparison with spontaneous uncatalyzed decarboxylation of OMP observed in water at neutral pH and ambient temperature. 11a,b Present in most species except viruses, ODCase exists as a monofunctional enzyme in bacteria and parasites and as a part of the bifunctional enzyme UMP synthase in human and other high-developed organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation